Psychological Impact Analysis and Critical Animation Creation: A Case Study of Thai Ghost Stratagems in Child Rearing - มีพัด, ธวัชชัย; แสงรัตนายนต์, ณัฐภณ; จาดสุวรรณ , กฤษณะ; ดีเจริญชิตพงศ์, จิรวิญญ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
Background and Significance: Traditional Thai child-rearing often utilizes "stratagems" based on ghost beliefs as tools for behavioral control, emphasizing fear over rational explanation. This approach significantly impacts psychological development; however, there remains a lack of concrete critical study through creative media. This creates a research gap regarding the communication of childhood trauma through visual arts. Therefore, the researcher selected animation as a medium due to its unique potential to transform abstract psychological states into tangible visuals, aiming to stimulate social awareness.           Objectives: 1) To study and analyze the use of fear as a cultural tool in Thai child-rearing; 2) To investigate the psychological impacts resulting from traditional ghost beliefs; and 3) To design and create a 2D motion animation as a form of social critique.           Methodology: This study employs a creative research methodology. It involves analyzing folklore and psychological data to develop a screenplay and visual style characterized by distorted imagery under an oppressive atmosphere. The production was executed using Adobe After Effects. Data collection instruments included quality assessment forms from three content experts and three media experts, as well as satisfaction surveys from a sample group of 30 individuals.           Results: The research findings indicate that the developed animation successfully transformed abstract psychological states into concrete visual forms. Quality assessments by content experts were at a High level (x̄= 3.83), and media experts rated the work at a "High" level (x̄= 4.63). Furthermore, satisfaction results from the sample group of 30 individuals were at a "High" level (x̄= 3.88). This project serves as a critical medium for examining fear-based parenting and encourages questioning the transmission of traditional stratagems that may leave long-term emotional scars on children.